A novel regulatory loop miR-101/ANXA2/EGR1 mediates malignant characteristics of liver cancer stem cells. (12th June 2020) - Ma, Sai; Cheng, Junping; Wang, Haiyan; Ding, Ningling; Zhou, Feng; Ji, Runing; Zhu, Li; Zhu, Chuanwu; Pan, Yunzhi
Abstract: Increasing evidence suggests that liver cancer stem cells (LCSCs) are the cellular determinants that promote tumor recurrence and metastases. Aberrantly expressed miRNAs were identified in LCSCs and found to play a significant role in modulating biological characteristics of LCSCs. In this study, we implemented miRNA microarrays in CD133 + LCSCs and found miR-101 expression was downregulated. Increasing miR-101 expression repressed the metastasis and tumorigenic potential in LCSCs. Further investigations showed that ANXA2 was a novel target of miR-101. And we revealed that ANXA2 plays a critical role in acceleration of cell cycle and enhancing the migration and invasion abilities of LCSCs. Elevated ANXA2 increased activation of extracellular signal-regulated kinase (ERK) which regulated SOX2 and cell cycle-related kinases. Moreover, ERK phosphorylation inhibited the expression of early growth response 1 (EGR1) which in turn restrained the transcription of miR-101. In vivo experiments, overexpression of miR-101 produced potent inhibitory effects on the growth of LCSCs xenograft tumors as well as ANXA2 knockdown. Taken together, our findings suggest a novel regulatory loop miR-101/ANXA2/EGR1 in LCSCs and may serve as potential therapeutic targets in liver cancer. Abstract : miR-101 was little known in liver cancer stem cells. Here, we found a novel miR-101/ANXA2/EGR1 regulatory circuit in LCSCs which lower miR-101 released ANXA2 expression. Elevated ANXA2 could suppress EGR1 which promoted miR-101 transcription through ERK pathway.